Effect of tuina on sleep quality, psychological state and neurotransmitter level in patients with insomnia: a systematic review and meta-analysis - Wang, Zhen; Xu, Hui; Wang, Zheng; Zhou, Hang; Zhang, Lijuan; Wang, Yu; Li, Miaoxiu; Zhou, Yunfeng (Frontiers in Neurology, 2024)
Background Abnormal psychological state and neurotransmitter levels are important factors affecting sleep quality. Numerous studies have shown that tuina can improve the symptoms of sleep disorders in patients with insomnia while relieving anxiety and depression and regulating neurotransmitter levels. However, there have been no meta-analyses on the effect of tuina on psychological states and neurotransmitter levels. Objectives A meta-analysis was performed to systematically evaluate the effects of massage on sleep quality, psychological state, and neurotransmitter levels in patients with insomnia. Methods A comprehensive literature search was conducted from inception to July 2023 using eight electronic databases to identify randomized controlled trials (RCTs) on tuina therapy for insomnia. Gray literature was also searched. The methodological quality of the included studies was assessed using the Cochrane Handbook. Reviewer Manager 5.4 and Stata 16.0 were employed for statistical analysis. Results A total of 23 studies were included, including 1780 patients with insomnia, of whom 892 and 888 were in the experimental and control groups, respectively. Meta-analysis indicated that tuina therapy was superior to other therapies for the treatment of insomnia in increasing the total effective rate [OR = 4.12, 95%CI (2.80, 6.06), p < 0.00001] and 5-hydroxytryptamine (5-HT) level [MD = 16.03, 95% CI (13.40, 18.65), p < 0.00001], while reducing the Pittsburgh Sleep Quality Index score [MD = −2.34, 95% CI (−2.94, −1.74), p < 0.00001], Athens Insomnia Scale score [MD = −2.10, 95% CI (−2.67, −1.52), p < 0.00001], self-rating anxiety scale score [MD = −6.77, 95% CI (−8.34, −5.20), p < 0.00001] and self-rating depression scale score [MD = −6.60, 95% CI (−8.82, −4.37), p < 0.00001]. Subgroup analysis showed that tuina alone or in combination with other therapies was superior to drugs or acupuncture alone in improving all outcomes (p < 0.05). Only two studies reported minor adverse events. Conclusion Tuina for insomnia has certain therapeutic advantages and can significantly improve sleep quality, relieve anxiety-depressive states, and increase 5-HT levels with high safety. Due to the limitations of the quality of the included studies, additional high-quality clinical trials are required for further verification. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=447839, identifier CRD42023447839.